2022
DOI: 10.3389/fpls.2022.853110
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Physiological, mRNA Sequencing, and miRNA Sequencing Data Reveals a Specific Mechanism for the Response to Continuous Cropping Obstacles in Pogostemon cablin Roots

Abstract: Pogostemon cablin (patchouli) is a commercially important medicinal and industrial crop grown worldwide for its medicinal and aromatic properties. Patchoulol and pogostone, derived from the essential oil of patchouli, are considered valuable components in the cosmetic and pharmaceutical industries. Due to its high application value in the clinic and industry, the demand for patchouli is constantly growing. Unfortunately, patchouli cultivation has suffered due to severe continuous cropping obstacles, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Drought stress causes lipid peroxidation and cell membrane damage due to ROS accumulation. Plants prevent cellular damage from ROS accumulation by increasing the activities of SOD and POD ( Yan W. P. et al., 2022 ). However, severe drought can lead to a decrease in the efficiency of the antioxidant defense system in plants, decreasing the activities of antioxidant enzymes such as SOD and POD ( Chen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Drought stress causes lipid peroxidation and cell membrane damage due to ROS accumulation. Plants prevent cellular damage from ROS accumulation by increasing the activities of SOD and POD ( Yan W. P. et al., 2022 ). However, severe drought can lead to a decrease in the efficiency of the antioxidant defense system in plants, decreasing the activities of antioxidant enzymes such as SOD and POD ( Chen et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs expression is affected by different stresses in plants which would regulate mRNA levels to respond to environmental alteration and affect plant development and growth [44,[51][52][53]. To clarify the targeted regulatory relationship between miRNAs and mRNAs, single miRNA to mRNA analysis or miRNA-mRNA integrated analysis are widely conducted [54,55]. In this study, we examined the miRNA expression alteration and its impact on target gene expression in the RL plants compared to the WT doner plants of rice cv.…”
Section: Discussionmentioning
confidence: 99%
“…Studies addressing the effects of continuous cropping have found that it has strong negative impacts on both plant and soil systems. These impacts include morphological, anatomical, physiological, and biochemical alterations in plants [11], altered soil microbial community structure [12], and accumulated allelopathic autotoxicity in the soil [13].…”
Section: Introductionmentioning
confidence: 99%